2005
DOI: 10.1590/s0004-27302005000100009
|View full text |Cite
|
Sign up to set email alerts
|

Hermafroditismo verdadeiro: experiência com 36 casos

Abstract: RESUMO (27,8%). O SRY foi negativo em todos os pacientes com cariótipo 46,XX e a gôna-da mais freqüentemente encontrada foi ovotéstis (OT-47%), seguida de ovário (OV-27%) e testículo (TT -24%). As associações mais freqüentes foram OV + TT (30,5%), OT + OT (22,2%) e OT + OV (22,2%). A opção do sexo de criação independeu do cariótipo, do tamanho do falo e da dosagem sérica de testosterona, mas foi influenciada pelo posicionamento do meato uretral, que, quando não era perineal (11 casos), levou todos à opção masc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Regardless of karyotype, roughly half of such newborns are assigned to the female gender and the other half to the male gender [65]. Some clinicians are particularly influenced in their gender decisions by the location of the urethral meatus and the associated surgical challenges [66], while others are led to favor female assignment by the frequent presence of a uterus and normal ovarian tissue as compared to the more frequently dysgenetic testicular tissue [67]. It is not surprising, therefore, that a number of case reports show gender dysphoria and/or patient-initiated gender change in either direction in patients with ovotesticular syndrome [68,69].…”
Section: Changes In Gender Assignment Policies For Newborns With Genimentioning
confidence: 99%
“…Regardless of karyotype, roughly half of such newborns are assigned to the female gender and the other half to the male gender [65]. Some clinicians are particularly influenced in their gender decisions by the location of the urethral meatus and the associated surgical challenges [66], while others are led to favor female assignment by the frequent presence of a uterus and normal ovarian tissue as compared to the more frequently dysgenetic testicular tissue [67]. It is not surprising, therefore, that a number of case reports show gender dysphoria and/or patient-initiated gender change in either direction in patients with ovotesticular syndrome [68,69].…”
Section: Changes In Gender Assignment Policies For Newborns With Genimentioning
confidence: 99%
“…This is strikingly different from the findings in patients with 46,XX testicular DSD (in which both gonads are testes), who are usually SRY-positive. In addition, SRY mutations leading to 46,XY OT-DSD are very rare [Walker et al, 2000;Domenice et al, 2001;Ortenberg et al, 2002;Damiani et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The author observed that 22% of the gonads had an incorrect diagnosis of testis or ovary from the biopsy when the correct diagnosis was ovotestis [6]. Therefore, the diagnosis of TH can be missed, especially in 46,XY DSD patients in whom histological studies of the gonads are not routinely performed [7]. …”
Section: Introductionmentioning
confidence: 99%